2021
DOI: 10.1039/d1bm00535a
|View full text |Cite
|
Sign up to set email alerts
|

3D bio-printed biphasic scaffolds with dual modification of silk fibroin for the integrated repair of osteochondral defects

Abstract: Repair of osteochondral defects is still a challenge, especially the regeneration of hyaline cartilage. Parathyroid hormone (PTH) can inhibit the hypertrophy of chondrocytes to maintain the phenotype of hyaline...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“…Methacrylated SF (SFMA) was synthesized as described previously [ 25 ]. Briefly, 40 g of silkworm cocoon was boiled in 2 L of 2% Na 2 CO 3 solution for 30 min at 100 °C and then washed several times with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Methacrylated SF (SFMA) was synthesized as described previously [ 25 ]. Briefly, 40 g of silkworm cocoon was boiled in 2 L of 2% Na 2 CO 3 solution for 30 min at 100 °C and then washed several times with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested that parathyroid hormone (PTH) inhibits chondrocyte hypertrophy and facilitates articular hyaline chondrogenesis. Deng et al (2021) used silk fibroin (SF) grafted with PTH by sulfonated SMCC (SF-PTH), covalently immobilized methacrylic anhydride (SF-MA), and photo-crosslinkable gelatin methacryloyl (GMA) for gradient strengthening of the scaffold based on natural mechanical strength. BMSCs were co-cultured separately in vitro with four bioinks (10% GM, 10% GM-5% SF, 10% GM-5% SF-MA, and 10% GM-5% SF-PTH).…”
Section: 3d Printingmentioning
confidence: 99%
“…All four bioinks had good biocompatibility, while GM + SF-PTH ink inhibited the hypertrophy of culutred chondrocytes. After implantation of GM + SF-PTH/GM + SF-MA scaffolds in rabbit distal femoral talar sulcus defects, higher macroscopic scores, and fewer specific markers of chondrocyte hypertrophy, were observed compared with controls, demonstrating that this mechanically graded bioprinted biphasic scaffold can effectively promote regeneration of osteochondral defects, while PTH helps maintain the phenotype of hyaline cartilage ( Deng et al, 2021 ).…”
Section: 3d Printingmentioning
confidence: 99%
“…Radial and circumferential (both outer and inner layers) tensile modulus readings showed that implants lagged behind native cartilage by margins of less than 5%. By contrast, Deng et al employed human parathyroid hormone (PH) to prevent chondrocyte hypertrophy in order to achieve and maintain hyaline-like properties (Deng, 2021). They achieved this using a biphasic, layered 3D bioprinted construct made of two distinct bioinks.…”
Section: Cell-based Bioprinting Of Knee Cartilagementioning
confidence: 99%